Thoracic perfusion of antiangiogenic agents combined with chemotherapy for treating malignant pleural effusion in non-small cell lung cancer: a network meta-analysis - Yan Xu; Wei Si; Yingying Cui; Liming Jiang; Yinan Yu; Xiaohua Zhu (BMJ Open)
Objectives Different intrathoracic perfusion therapeutic regimens are available for non-small cell lung cancer with malignant pleural effusion (MPE). Antiangiogenic agents are often used to control MPE, and the results are satisfactory. Here, we performed a network meta-analysis to reveal optimal combinations of antiangiogenic agents and chemical agents and assess their effectiveness and safety.Design Systematic review and network meta-analysis.Data sources PubMed/Medline, Embase, Cochrane, Web of Science, Wanfang, VIP Database and Chinese National Knowledge Infrastructure were searched from inception to May 2023. Eligible studies were randomised controlled trials that reported on curative effect of MPE.Data extraction and synthesis The Cochrane Collaboration tool was used to assess risk of bias. The consistency was evaluated by examining the agreement between direct and indirect effects. Network meta-analysis was performed and the ranking probabilities of being at each possible rank for each intervention were estimated. Comparison-adjusted funnel plots were obtained to assess publication bias.Results A total of 46 studies were included in the analysis. Among them, we included a total of seven interventions. A total of 3026 patients participated in this analysis. According to the results of the network meta-analysis, some antiangiogenic agents combined with chemotherapy regimens improved objective response rate (ORR) and disease control rate (DCR) and quality of life (QOL). The rank probabilities suggested that in terms of ORR, DCR and QOL, Endostar plus lobaplatin was the first-ranked intervention.Conclusion Administration of antiangiogenic agents plus chemical agents significantly improved the clinical response and QOL. In addition, Endostar plus lobaplatin was the most effective combination.PROSPERO registration number CRD42021284786.